Gain-phase analyzer using the Z8F6401 microcontroller - Italia, Mary Rose Diwata L. (2004)
Devices which obtains the frequency response curves are very important in the analysis and design of control systems. However, such devices cost about [Dollar sign]20,000 - [Dollar sign]27,000. This project aims to develop an alternative to these devices which will only cost less than 10,000 pesos. The device is called Gain-Phase Analyzer and it was implemented using Zilog's Z8F6401 microcontroller. The Gain-Phase Analyzer acquires the frequency of a given plant and generates the bode plot on an oscilloscope. The range of the magnitude plot is from -40dB to +40dB. The range of the phase plot is from 0 yo -360 degrees. The frequency on the x-axis is from 1 Hz to 1 kHz. Log-spacing is used to distribute the frequency steps and there are 5-20 frequency points per decade. The Z8F6401 microcontroller and the AD0820 digital-to-analog converter function as a sweep sine generator. The sweep sine generator sweeps the frequency of the input from fstart to fstop. The sine wave at each frequency is fed to the plant to be characterized. This input signal and the corresponding output of the plant will be captured by the Z8F6401 through the MAX114 analog-to-digital converter. Data manipulations are done by a software stored in the Flash program memory. The software is a compiled C-code developed through the ZDS II IDE with ANSI C-Compiler that comes with the Z8 Encore Development Kit. This software converts the Fourier transform of the signals. After the computations, the gain and phase vectors will be displayed using the two separate channels of the oscilloscope. The Z8F6401 microcontroller was chosen for its memory and high-performance register-to-register architecture. Also, the reduced total system cost when using the Zilog Encore board made it more affordable to mass-produce the project. Among the Z8 Encore family, Z8F6401 board was chosen because its 64K Flash and 4K RAM memory are enough to store the software and the data points. It has also enough I/0 lines needed for this application. The Gain-Phase Analyzer can be used for the characterization of control systems and for other instructional purposes.